Novel modified quantitative index for cone-beam CT assessment of medication-related osteonecrosis of the jaw - comparative analysis with original index - Ghaidaa Badabaan; Maxine Strickland; Steven R Singer; Adriana G. Creanga; Gayathri Subramanian (Saudi Dental Journal)
Purpose: The main research goal was to address the critical need for an objective and quantitative index to describe the nature and extent of radiographic features of medication-related osteonecrosis of the jaw (MRONJ) lesions and complement the descriptive radiographic interpretation of the lesion and its clinical assessment. Method and Materials: A retrospective review of MRONJ patients assessed at our institution was performed to compare the Composite Radiographic Index (CRI), identified from a prior scoping review, with a proposed modification, the Modified CRI index (‘Mod-CRI’). The Mod-CRI index was weighted to assign a higher score for diffuse radiographic involvement of a given lesion, and delineated MRONJ lesions into those with ‘high’ and ‘low’ severity. Twenty-two MRONJ cases imaged with CBCT were retrospectively assessed with both CRI and Mod-CRI indices and the two indices were compared for their ability to quantitatively describe cone-beam computerized tomography (CBCT) radiographic features and complement the clinical staging of the MRONJ lesion. Results: There was a statistically significant association between increased clinical stage and higher mod-CRI score (p = 0.040). The Mod-CRI index sorted the patients who scored intermediate scores with the CRI (n = 15) into either the low (n = 8) or high categories (n = 7). Conclusion: The Mod-CRI index eliminated the ambiguous intermediate-category-scores in the previously published CRI index and provided greater clarity to the interpretation of a given index score. Adopting the Mod-CRI could improve MRONJ assessment and enhance communication between the radiologist and the clinician.